Small Genres of Scientific Style and Methods of Teaching Them (Eurasian Journal of Philology Science and Education, 2025)
Nowadays in the context of the rapid development of science and technology, the number of scientific works and scholarly literature has been steadily increasing each year. In an era full of uninterrupted flows of information, it is no longer sufficient merely to understand the language of scientific texts, it is crucial to foster a generation capable of critically evaluating them and forming independent viewpoints. In this regard, it's obvious that the systematic development of such competencies begins with school learners.The article reviews the perspectives of domestic and foreign scholars on the classification of the scientific style into its internal subtypes. It distinguishes the linguistic and structural characteristics, as well as the stylistic features, of the pure scientific substyle, the popular-scientific substyle, and the scientific-textbook substyle. It is revealed that there is still no unified or consistent position among researchers regarding the subdivision of scientific style into substyles.Although all subtypes of scientific style strictly adhere to linguistic norms, are based on scientific principles, and present information that is accurate, precise, and grounded in objective data, each of them is nevertheless oriented toward a specific target audience. In this context, tenth-grade students examined the linguistic features of scientific texts from the standpoint of the addressee. An experiment was conducted to identify the key difficulties that impede learners’ acquisition of linguistic units used for conveying scientific information, as well as their ability to communicate freely and develop speaking skills in scientific language. The results of a specially designed questionnaire made it possible to assess students’ level of mastery of linguistic tools and terms, new vocabulary while working with scientific texts. The conclusions drawn from the experiment will serve as the basis for developing a set of tasks aimed at improving effective methods for teaching scientific texts in the future.Keywords: scientific style, substyles of scientific style, pure scientific substyle, popular-scientific substyle, scientific-textbook substyle, teaching, methods of teaching.